That should still be us : how Thomas Friedman's flat world myths are keeping us flat on our backs - Sieff, Martin. (Wiley, 2012)
"Chronicles the damage Thomas Friedman's flat wrong, "Flat Earth" ideas have caused to the American economyAs Martin Sieff convincingly argues, Thomas Friedman's prescriptions have played a major role in causing America's economic decline, yet many executives and politicians, including President Obama, still look to him as their guru. Sieff exposes Friedman fallacies on the nature of globalization, the information technology revolution, political paralysis in Washington, and energy consumption. He documents how China is investing far more in locking up the world's oil and gas reserves than in developing the ineffective green technologies Friedman claims they love. He exposes Friedman's most acclaimed ideas as retreads of na??ve fantasies widely believed and exposed as useless a century ago. Convincingly refutes Thomas Friedman's fantasies and many fallacies in his best-selling books, The World is Flat and That Used to Be Us, and presents a radically different vision and road map for America's economy and its future Offers a practical trade and energy strategy to restore American prosperity and industrial strength in the twenty-first century Explains why America's economy will soon depend on producing low-carbon footprint natural gas, reviving its manufacturing sector, and protecting its industry from unfair foreign competition and artificially manipulated exchange rates Written by veteran journalist Martin Sieff, a regular contributor to FoxNews.com and Chief Global Analyst at The Globalist Research Center "--